Case report of unusual synchronous anal and rectal squamous cell carcinoma: clinical and therapeutic lesson - Ciardiello, Davide; Del Tufo, Sara; Parente, Paola; Gravina, Antonietta Gerarda; Selvaggi, Francesco; Panarese, Iacopo; Franco, Renato; Caterino, Michele; Martini, Giulia; Ciardiello, Fortunato; Grassi, Roberto; Cappabianca, Salvatore; et al. (Frontiers in Oncology, 2023)
Synchronous tumors of the rectum and anus are sporadic. Most cases in the literature are rectal adenocarcinomas with concomitant anal squamous cell carcinoma. To date, only two cases of concomitant squamous cell carcinomas of the rectum and anus are reported, and both were treated with up-front surgery and received abdominoperineal resection with colostomy. Here, we report the first case in the literature of a patient with synchronous HPV-positive squamous cell carcinoma of the rectum and anus treated with definitive chemoradiotherapy with curative intent. The clinical-radiological evaluation demonstrated complete tumor regression. After 2 years of follow-up, no evidence of recurrence was observed.